2004
DOI: 10.1056/nejmoa032651
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Laparoscopically Assisted and Open Colectomy for Colon Cancer

Abstract: In this multi-institutional study, the rates of recurrent cancer were similar after laparoscopically assisted colectomy and open colectomy, suggesting that the laparoscopic approach is an acceptable alternative to open surgery for colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
491
7
12

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,010 publications
(551 citation statements)
references
References 18 publications
25
491
7
12
Order By: Relevance
“…However, it is within the reported range (15 to 30 %) [6,8,37,38]. The reported hospital stay after laparoscopic CRC surgery is 5 to 8 days [6,8].…”
Section: Open Surgery Vs Laparoscopysupporting
confidence: 50%
See 2 more Smart Citations
“…However, it is within the reported range (15 to 30 %) [6,8,37,38]. The reported hospital stay after laparoscopic CRC surgery is 5 to 8 days [6,8].…”
Section: Open Surgery Vs Laparoscopysupporting
confidence: 50%
“…However, it is within the reported range (15 to 30 %) [6,8,37,38]. The reported hospital stay after laparoscopic CRC surgery is 5 to 8 days [6,8]. In a meta-analysis of 7 trials, hospital stay after laparoscopic colon and rectal cancer resection has been analyzed separately and shown to be significantly shorter in both groups [35].…”
Section: Open Surgery Vs Laparoscopymentioning
confidence: 74%
See 1 more Smart Citation
“…Postoperative complications are observed in around 20% of patients who receive curative surgery with lymph node dissection for colorectal cancer 3, 4, 5, 6. Recent studies have shown that the postoperative complications were risk factors for the survival or disease recurrence in various types of malignancies 7, 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a subset analysis of a randomized trial showed a lower recurrence rate and better survival in patients with stage III colon cancer undergoing laparoscopic surgery compared with open surgery 13, 14, 15, 16, 17. In those studies, no additional procedure to cover serosal invasion to prevent the detachment of cancer cells to the peritoneal cavity was used during surgery in either approach.…”
Section: Discussionmentioning
confidence: 99%